2015
DOI: 10.1002/chem.201503828
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Phenothiazine‐Based Platinum(II)–Acetylide Photosensitizers for Efficient Dye‐Sensitized Solar Cells

Abstract: Three new unsymmetrical phenothiazine-based platinum(II) bis(acetylide) complexes PT1-PT3 with different electron-donating arylacetylide ligands were synthesized and characterized. Their photophysical, electrochemical, and photovoltaic properties have been fully investigated and the density functional theory (DFT) calculations have been carried out. Under AM 1.5 irradiation (100 mW cm(-2)), the PT1-based dye-sensitized solar cell (DSSC) device exhibited an attractive power conversion efficiency (η) up to 5.78 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Polymetallynes have long been studied as photoactive materials. ,,,, , The ease of modifying the alkynyl ligands, coupled with triplet-state photophysics in solution and the solid state, lends them to a variety of applications, including organic light emitting diodes (OLEDS), optoelectronics, sensors, ,, and nonlinear optics (NLO), among others. , Much of this work has focused on polymeric and multinuclear Pt­(II) complexes. In these d 8 species, the heavy-metal atom facilitates intersystem crossing to the triplet excited state manifold.…”
mentioning
confidence: 99%
“…Polymetallynes have long been studied as photoactive materials. ,,,, , The ease of modifying the alkynyl ligands, coupled with triplet-state photophysics in solution and the solid state, lends them to a variety of applications, including organic light emitting diodes (OLEDS), optoelectronics, sensors, ,, and nonlinear optics (NLO), among others. , Much of this work has focused on polymeric and multinuclear Pt­(II) complexes. In these d 8 species, the heavy-metal atom facilitates intersystem crossing to the triplet excited state manifold.…”
mentioning
confidence: 99%
“…The DFT computational data on P1 and P2 indicated that the atomic contributions of the HOMO were significantly larger on [Pt] , which then suggest that this moiety represents the electron-donor segment of the polymers during the electron transfer. This conclusion is unprecedented and could explain the large number of literature works using this synthon for the construction of solar cells. Using 1:1 polymer/PCBM films, fs-TAS established that the k et values are ultrafast (time scale ≤150 fs; IRF limit).…”
Section: Discussionmentioning
confidence: 94%
“…The trans -bisethynylbis­(trialkylphosphine)­platinum­(II) building block, [Pt] , is a versatile unit for the design of photonic materials showing potential applications in nonlinear optics and light-emitting diodes. In the field of solar cells, the [Pt] -containing materials are also active irrespective of whether they are used as molecules or within polymer chains. , Indeed, dye-sensitized solar cells and bulk heterojunction solar cells (BHJSCs) were designed. To the best of our knowledge, the highest photoconversion efficiency (PCE) was recently reported to be 5.29% for a BHJSC containing the [Pt] moiety. , Concurrently, studies on complexes bearing [Pt] units indicated that the charge separated states are formed in the short picosecond (ps) time scale and that the [Pt] unit could mediate the electron transfer. Over the years, it was suggested that anchoring diphenylamine pendants as electron-rich groups , and using the electron-deficient anthraquinone, AQ , moiety , should improve the PCEs of [Pt] -containing materials for solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Such a strategy has been a successful approach to realize binary and even ternary memory performance. [1e,3] Given the synthetic versatility and interesting spectroscopic features, platinum(II) complexes have been extensively studied for various applications including but not limited to photoswitchable materials, [4] photosensitizers, [5] biolabelling agents, [6] and organic light-emitting diodes (OLEDs). [7] While cyclometalated platinum(II) complexes represent one of the topical interests, their application studies as organic resistive memories remain rather unexplored.…”
Section: Introductionmentioning
confidence: 99%